2007
DOI: 10.1590/s1413-70542007000600035
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de forrageiras de inverno irrigadas sob pastejo

Abstract: RESUMOO experimento foi conduzido na UNESP -Jaboticabal com o objetivo de obter informações sobre o rendimento de matéria seca (RMS) e composição química das forrageiras de inverno, aveia preta (Avena strigosa Schreb) e triticale (X Triticosecale Wittmack), em plantio direto sob palhada de área com milheto (Pennisetum americanum (L.) K. Schum.) ou híbrido sorgo sudão (Sorghum bicolor (L.) Moench x Sorghum sudanense (Piper) Stapf) submetidas a pastejo. A forragem foi rebaixada por vacas da raça Holandês. O deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 1 publication
3
10
0
3
Order By: Relevance
“…Such decrease in dry matter production during the evaluation periods was also observed in cutting and grazing management practices by Moreira et al (2007), who worked with winter forage, irrigated under grazing. They assumed that this decrease is caused by the advanced stage of plants development, which caused the elimination of apical meristems and damage to a new sprouting.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Such decrease in dry matter production during the evaluation periods was also observed in cutting and grazing management practices by Moreira et al (2007), who worked with winter forage, irrigated under grazing. They assumed that this decrease is caused by the advanced stage of plants development, which caused the elimination of apical meristems and damage to a new sprouting.…”
Section: Resultssupporting
confidence: 64%
“…When periods were compared, this feature showed no significant difference. Moreira et al (2007) worked on oat genotypes and also observed no significant differences between periods for the variable cellulose.…”
Section: Resultsmentioning
confidence: 86%
“…A utilização de gramíneas de clima temperado como alternativa para amenizar a sazonalidade da produção de forragem tem sido bastante estudada (Veasey et al, 1977;Ferolla et al, 2007;Ruiz et al, 2007;Moreira et al, 2007).…”
Section: Introductionunclassified
“…As gramíneas tropicais apresentam insuficiência produtiva e qualitativa, principalmente no Brasil Central, principalmente, em decorrência da escassez pluviométrica e das baixas temperaturas no período de inverno (Moreira et al, 2007). No entanto, o uso da irrigação segundo Ribeiro et al (2009), existem forrageiras que respondem muito bem ao uso da irrigação, proporcionando maior produção de biomassa.…”
Section: Methodsunclassified